2019
DOI: 10.3390/su11205566
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Self-Rated Health among Older Adults Living in Urban China: A Mediation Model

Abstract: Social capital and healthy aging are both crucial for social sustainability in China. The present study tested the role of structural social capital in self-rated health among older urban Chinese adults and the influence of cognitive social capital on this relationship. A sample of 456 older adults aged 60 or older in Suzhou, China, were recruited and completed the survey in 2015. Structural equation modeling was used to test the proposed model. Cognitive social capital had larger effects on self-rated health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Consistent with the findings of previous studies [ 10 , 11 , 12 ], the findings of this study suggest that higher levels of cognitive social capital indicate higher levels of trust, reciprocity, and a sense of belonging to local communities, while higher levels of structural social capital foster higher frequencies of social participation, more organization memberships, and more volunteering and citizenship activities in rural China. Previous studies have indicated that some social capital indicators (e.g., a sense of belonging and familiarity, trust, and organization memberships) are significant factors of aging in place [ 1 , 2 , 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the findings of previous studies [ 10 , 11 , 12 ], the findings of this study suggest that higher levels of cognitive social capital indicate higher levels of trust, reciprocity, and a sense of belonging to local communities, while higher levels of structural social capital foster higher frequencies of social participation, more organization memberships, and more volunteering and citizenship activities in rural China. Previous studies have indicated that some social capital indicators (e.g., a sense of belonging and familiarity, trust, and organization memberships) are significant factors of aging in place [ 1 , 2 , 3 , 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…This strategy would not only promote intergenerational relationships but also help elderly individuals’ families to mitigate the burden of caregiving. Furthermore, interventions such as information sharing in regard to daily care services and long-term health, crisis interventions, peer support programs, and volunteering programs should be developed to achieve healthy aging [ 12 ], promote intergenerational solidarity [ 35 ], and encourage the young-old to care for old-old groups [ 6 ]. Finally, expanding access to health and service resources in the community is crucial for meeting the long-term care needs of older residents and enhancing the efficiency of social capital (e.g., transferring information and resources).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations between cognitive and structural aspects of social capital have been identified in the literature [40][41][42][43]. These causal relationships could be bidirectional.…”
Section: Cognitive Social Capital Structural Social Capital and Mental Healthmentioning
confidence: 99%
“…The assessment of SRH is not only easy to implement in research and clinical settings but also has proved to be valid across culture and countries [ 4 , 6 ]. The literature has identified significant factors of SRH, such as age, gender, socioeconomic status, and physical health [ 4 , 5 , 7 , 8 , 9 ]. Furthermore, proponents of the resource hypothesis suggested that people’s subjective assessments of their general health status are affected by not only the severity of illness and family history but also external supportive resources from families and communities [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%